Effects of previous coronary artery bypass graft surgery on in-hospital mortality in ST-segment elevation myocardial infarction: National dataset analysis. (October 2021) - Pancholy, Samir B.; Patel, Purveshkumar; Patel, Gaurav A.; Patel, Dhara D.; Patel, Neil R.; Pattara, Elizabeth A.; Patel, Tejas M.
Highlights: STEMI patients with previous CABG have a higher in-hospital mortality. Primary PCI use is increasing in STEMI patients with or without CABG. Primary PCI improves in-hospital mortality in STEMI patients with CABG. A trend of increasing adverse outcomes is observed in STEMI patients with CABG. Abstract: Background: Association of history of coronary artery bypass graft surgery (CABG) with clinical outcomes in patients presenting with ST-segment elevation myocardial infarction (STEMI) is unclear from current data. Methods: Using Nationwide Inpatient Sample (NIS) data from 2003 to 2014, adult patients hospitalized with principal diagnosis of STEMI were extracted. The cohort was divided into patients with a history of CABG and those without a history of CABG. The primary outcome measure was in-hospital mortality (IHM). Results: 2, 710, 375 STEMI patients were included in final analysis of which 110, 066 had history of CABG. Patients with history of CABG had higher unadjusted (12.2% vs. 8.8%, P < 0.001) and adjusted (odds ratio [OR]1.16; 95% confidence interval [CI] 1.14 to1.19, P < 0.001) IHM compared to those without previous CABG. Compared to a trend of decreasing IHM in STEMI patients without previous CABG, a trend of increasing IHM was observed over the study period in those with a history of previous CABG. Although patients with previous CABG when treated with primary PCI (PPCI) had a higher unadjusted IHM compared to those without previous CABG, (4.8% vs 4.3%, P < 0.001), after adjusting for comorbidities and in-hospital complications no significant increase in IHM was observed in patients with previous CABG treated with PPCI. Conclusion: STEMI patients with previous CABG have a significantly higher IHM compared to those without previous CABG. PPCI improves IHM with no independent mortality disadvantage attributable to previous CABG.